Deep sea dive - Lampard, Frank (London: Little, Brown Books for Young Readers, 2016)
Frankie and his team love playing football. There's always time for a game. And now that they have their magical football they're playing against teams they never imagined! During a visit to a holiday park, Frankie and his friends discover a theme park with a difference - each ride is a portal into an amazing fantasy world. This time, the magic football takes them all on an underwater adventure that asks Max to swim his best doggy paddle, and makes playing football a game against the tide!
Keywords: Children's stories